Waste Cassava as Brick Additive. (Building Material Innovation for Green Architecture) - Kuasuma Y; Munawaroh A S (International Conference on Engineering and Technology Development (ICETD), 2017)
The concept of green architecture that is identical to the natural shades is not limited to the design but the type and origin of building materials that were presented be part of the concept, as well as continuous innovation among which the industrial solid limah processing tapioca into charcoal, as additives block making. By the nature of the charcoal pozzolan is a material containing silica, assists in the binding reaction between the cement with aggregate filler paste adobe. The test results obtained specimen strength - average of adobe around 711,5kg / cm2, equivalent to B1 quality, this quality brick is the standard used to carry the load in construction. While the tangible benefits gained from this product is more environmentally friendly waste utilization results potentially pollutant or tapioca as product innovation and applicable for the construction of green architecture.